Responses of Rumex obtusifolius L. to several 'hormone' herbicides : being a thesis submitted in partial fulfilment of the requirements for the degree of [Master of] Agricultural Science, University of New Zealand, Massey Agricultural College - Templeton, John Keith (Massey Agricultural College, 1952)
Weeds have been a problem to man ever since he began to till the soil. Their presence is a factor lowering yield and increasing the cost of production of almost every economic crop. Weed eradication and control measures therefore, are bound to loom large in the management of crops at various stages throughout their growing period. Following upon such discoveries as those of Slade et al (1) and Mitchell and Hamner (2) that synthetic growth-regulating substances possessed properties capable of causing violent and often fatal disturbances to plant growth, new and effective methods of destroying undesirable species were developed. In fact, it can be said that the whole thought and practice of weed control was revolutionized by the promotion of certain practical aspects proceeding from the rapidly accumulating knowledge of plant-growth substances. [FROM INTRODUCTION]
Keywords: New Zealand; Docks (Plants); Weeds; Control; Effect of herbicides on plants